Traffic Unit Educational Communication Strategy in an Effort to Reduce Accident Cases in the Jurisdiction of the Waru Sector Police, Penajam Paser Utara Regency - Kiswoyo, Triyan; Sukmarini, Andi Vita; Mujahid, Mujahid (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study examines the effectiveness of the education communication strategy implemented by the Waru Police Traffic Unit in reducing the number of traffic accidents in Penajam Paser Utara Regency, an area known for its high number of traffic accidents. The focus of the study is on the education communication strategy implemented by the Waru Police Traffic Unit in the context of its specifications, and to reveal factors that influence the effectiveness of communication in an effort to reduce the number of traffic accidents in Penajam Paser Utara Regency. A qualitative approach with a qualitative descriptive research type and case study is the method used in the study. Data collection through in- depth interviews, direct observation, and document analysis to further explore the communication strategy of the Waru Police Traffic Unit, understand the experiences and perceptions of the community and members of the Traffic Unit regarding traffic education communication, and study the social and cultural context in the Penajam Paser Utara Regency area that influences people's traffic behavior. Based on the research results, efforts to implement traffic unit education strategies can reduce accident cases in the jurisdiction of the Waru Police, Pejajam Paser Utara Regency. Efforts made include cross- sector cooperation, law enforcement by conducting raids and patrols, counseling and education, and infrastructure improvements. Efforts made by involving the community directly so that traffic unit education can be conveyed and become an effort to reduce the number of accidents in the jurisdiction of the Waru Police Sector, Penajam Paser Utara Regency.